Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Metode Peta Konsep Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas III Sekolah Dasar Negeri 65/II Sungai Bangsat Bungo - Wiseza, Fitria Carli; Marza, Iber; Nelis, Selvia; Putri, Aura Nabila (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2021)
This research was conducted aiming to improve student learning outcomes through the concept map method in learning activities. The type of research in this thesis is Classroom Action Research (CAR). The research subjects were third grade students of SDN 65/II Sungai Bangsat Bungo, totaling 24 students, 12 male students and 12 female students. This research includes 2 cycles. Each cycle consists of 4 stages in its implementation, namely planning, implementing actions and observations, and reflection. For data collection techniques in the form of observation sheets, interviews, and learning outcomes tests. And the data analysis technique in the form of an assessment scale includes 4 categories of learning achievement achievement. The results of the study obtained an increase in student learning outcomes in Cycle I by 58% which was in the fairly good category and increased again in Cycle II to 88% in the very good category of the total number of third grade students at SDN 65/II Sungai Bungo bastard. Based on the results of the study, it was concluded that the concept map method carried out during learning activities had been proven to improve the learning outcomes of third grade students at SDN 65/II Sungai Bangsat Bungo.